Effects of Two Combinations of Multi-purpose Species Plantations on Imperata cylindrica in Restoring Site, Northern Thailand - Kaewkrom, Puangpaka; Gajaseni, Jiragorn (Indian Forester, 2006)
Due to a growing population and their demands for agricultural land, as well as a high demand for timber products, especially Teak, large areas of forest ecosystem have been disturbed leaving behind them land of little use. Many of these abandoned areas have been invaded by secondary successional species, such as the grass Imperata cylindrica which is aggressive, economically worthless, and ecologically undesirable because they prevent the establishment of more desirable species. The use of multi-purpose species plantation, which is a form of forest management, was an effort to solve this problem in Thailand's northern region. The objectives of this research, focused on the effects of two multi-specific plantations on plant species diversity and density of Imperata cylindrica. Results of this research indicated that the two-species plantation had a higher floristic diversity of both woody and non-woody species in their understorey than the single-species plantation. However, focusing only on the density of grasses, the mixed-species plantation (TG) was also more effective than the singlespecies plantation in suppressing aggressive weeds and grasses. Furthermore, if the management goal is to regenerate forest with a high diversity of tree species similar to those in native mature forests, a mixed plantation is more effective than a single-species plantation